The effect of periodontal and peri-implanter health on IL-1β and TNF-α levels in gingival crevicular and peri-implanter sulcus fluid : a cross-sectional study : a cross-sectional study = El efecto de la salud periodontal y peri-implantar en niveles de IL-1β y TNF-α en el fluido crevicular y sulcus peri-implantador : un estudio transversal. - Gündoğar, Hasan; Uzunkaya, Meral (2021)
It is stated that peri-implanter diseases have destructive effects similar to periodontal diseases. This study aims to compare IL-1β and TNF-α levels in healthy and diseased areas. Forty non-smokers systemically health individuals (40 implants/40 teeth) (age:38-67) were included in the study. In clinical and radiographic examinations; plaque index (PIn), gingival index (GI), periodontal pocket depth (PPD), clinical attachment level (CAL) and marginal bone loss (MBL) values were recorded. The gingival crevicular fluid (GCF) and peri-implanter sulcus fluids (PISF) of the patients were collected, and IL-1β and TNF-α levels were measured by ELISA in the samples. The collected data were analyzed with the help of SPSS v.22 package program. Sample PPD score showed a statistically significant difference between the diseased and healthy groups and also sample CAL showed statistically significant higher in Periodontitis(P) compared to periodontally heathy(H) and Gingivitis(G) (p>0.05). IL-1beta and TNF-α levels in GCF/PISF; In the P and Peri-implantitis (PI) group, it was found statistically significantly higher than the H, Healthy-Implant (HI), besides P showed higher levels compared to G (p<0.05). Within the limitations of our study, it can be said that IL-1β and TNF-α among inflammatory cytokines in GCF/PISF will increase in periodontal and peri-implanter diseases, it can also be said that this increase in cytokines may indicate that periodontal and peri-implanter diseases have similar immunological structure. Peri-implant mucositis without periodontitis history has similarity to peri-implantitis and periodontitis in terms of IL-1β and TNF-α levels in GCF/PISF.
Se afirma que las enfermedades peri-implantarias tienen efectos destructivos similares a los de las enfermedades periodontales. Este estudio tiene como objetivo comparar los niveles de IL-1β y TNF-α en zonas sanas y enfermas. Cuarenta individuos no fumadores con salud sistémica (40 implantes/40 dientes) (edad:38-67) fueron incluidos en el estudio. En los exámenes clínicos y radiográficos se registraron los valores de índice de placa (PIn), índice gingival (GI), profundidad de la bolsa periodontal (PPD), nivel de fijación clínica (CAL) y pérdida de hueso marginal (MBL). Se recogieron los fluidos creviculares gingivales (GCF) y los fluidos del surco peri-implantario (PISF) de los pacientes, y se midieron los niveles de IL-1β y TNF-α mediante ELISA en las muestras. Los datos recogidos fueron analizados con la ayuda del programa de paquete SPSS v.22. La puntuación PPD de la muestra mostró una diferencia estadísticamente significativa entre los grupos enfermos y sanos y también la muestra CAL mostró estadísticamente significativa más alta en la Periodontitis (P) en comparación con la salud periodontal (H) y la Gingivitis (G) (p>0.05). Los niveles de IL-1beta y TNF-α en GCF/PISF. En el grupo de P y Peri-implantitis (PI), se encontró estadísticamente significativo más alto que el H, implante sano (HI), además P mostró niveles más altos en comparación con G (p<0.05). Dentro de las limitaciones de nuestro estudio, se puede decir que IL-1β y TNF-α entre las citoquinas inflamatorias en GCF/PISF aumentarán en las enfermedades periodontales y peri-implantarias. También se puede decir que este aumento de citoquinas puede indicar que las enfermedades periodontales y peri-implantarias tienen una estructura inmunológica similar. La mucositis peri-implantaria sin antecedentes de periodontitis tiene similitudes con la peri-implantitis y la periodontitis en cuanto a los niveles...
En revista Odóvtos, vol. 23, no.1 (enero-abril 2021)
Descripción basada en el contenido visto el 29 de octubre, 2024
También disponible en formato HTML y EPUB